Study on the decomposition conditions of gas hydrate in quartz sand-brine mixture systems. (April 2019) - Wang, Xiao-Hui; Wang, Yun-Fei; Xie, Yan; Sun, Chang-Yu; Chen, Guang-Jin
Highlights: H-L-V conditions were determined by isothermal stepwise depressurizing method. The decomposition pressure varies in a small range at specific temperature. The equilibrium conditions are influenced by uneven distribution of pore size. Pore water salt concentration is a dominant factor on H-L-V conditions. Abstract: There are huge reserves of natural gas hydrates, a type of low-carbon energy resource, and it is considered important to study the stability conditions of hydrates in situ, to facilitate reserve evaluation and exploitation. The decomposition conditions of methane hydrate were determined in a quartz sand-brine mixing system, using an isothermal, stepwise, depressurising method. Influencing factors, such as sand particle size and pore water salt concentration, and the combined effect of these factors on the hydrate phase equilibrium, were investigated. The results showed that the decomposition pressure was distributed over a small range, and at specific temperatures. This may be partly related to the uneven distribution of pore size, but was shown to be mainly owing to the change of salt concentration during hydrate dissociation, as verified by differential scanning calorimetry. In addition, the hydrate dissociation pressure increased slightly with decreased particle size, and the maximum relative deviation of the dissociation pressure was 1.68%, when the sand particle size was within 100 mesh, which was mathematically negligible. For predicting the decomposition condition of hydrate in the quartz sand-brine mixing system, commercially-available CSMgem and PVTsim software showed high accuracy across a large temperature interval. An in-house, Chen-Guo hydrate model was valid when the temperature was below 277 K, while the Multiflash programme exhibited too large an error to be applied to this system.